Manganese–cobalt based spinel coatings processed by electrophoretic deposition method: The influence of sintering on degradation issues of solid oxide cell oxygen electrodes at 750◦c - Zanchi, Elisa; Ignaczak, Justyna; Kamecki, Bartosz; Jasinski, Piotr; Molin, Sebastian; Boccaccini, Aldo R.; Smeacetto, Federico (Materials, 2021)
This paper seeks to examine how the Mn–Co spinel interconnect coating microstructure can influence Cr contamination in an oxygen electrode of intermediate temperature solid oxide cells, at an operating temperature of 750◦C. A Mn–Co spinel coating is processed on Crofer 22 APU substrates by electrophoretic deposition, and subsequently sintered, following both the one-step and two-step sintering, in order to obtain significantly different densification levels. The electrochemical characterization is performed on anode-supported cells with an LSCF cathode. The cells were aged prior to the electrochemical characterization in contact with the spinel-coated Crofer 22 APU at 750◦C for 250 h. Current–voltage and impedance spectra of the cells were measured after the exposure with the interconnect. Post-mortem analysis of the interconnect and the cell was carried out, in order to assess the Cr retention capability of coatings with different microstructures.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Chromium poisoning; Electrophoretic deposition; Manganese–cobalt spinel; Solid oxide cell